Building BLOCS and stepping stones: Combined data for international economic and policy analysis - Jennifer Pédussel Wu; Clark N. Banach; Sofoklis Goulas; Ignacio Silva Neira (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2024)
The question of whether trade agreements are 'stepping stones' or 'stumbling blocks' to multilateral trade liberalization is not a new one; however, the empirical methods and the quality of the data used to address this question are continually improving. This paper explores this familiar question using a robust combined dataset and advances in structural gravity analysis to offer insight into regional integration agreements and trade networks. We introduce the Bilateral Longitudinal Observations and Country Statistics (BLOCS) database and demonstrate variation in PPML estimations using measures from varying sources. The data includes observations between 218 sovereign states, and their trading partners, over 60 years (1963-2022). We estimate specifications using four measures of trade flows, and several trade agreement dummies, accounting for varying definitions and reporting practices. Observations also include information on agreement depth and country attributes to contextualize existing literature and further understand the relationship between international trade and agreements. Differences observed between measures of Regional Trade Agreement (RTA) pairs indicate that the methodology for coding trade agreement participation matters. Our findings also suggest that variations in agreement details predict variation in total trade, thus supporting the hypothesis that not all trade agreements are created equal. It is the institutional details that determine whether a trade agreement will be a 'stepping stone' or a 'stumbling block' to multilateral trade liberalization.
Keywords: C80; C89; D02; F02; F14; F15; 330; Database; Empirical gravity models; International trade; Regional trade patterns